Peran Santri Dalam Mendukung Pembangunan Berkelanjutan (SDGS) Melalui Pengembangan Pendidikan Berbasis Life Skill Di Pesantren - Mujiburrohman Mujiburrohman (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2024)
Indonesia as one of the countries that has agreed on the implementation of Sustainable Development Goals (SDGs) is committed to the successful implementation of the SDGs through various activities and has taken strategic steps. The purpose of this study is to determine the role of santri in sustainable development (SDGs). This research method uses a literature review study (SLR) by examining various sources such as books, articles and others. The source search method uses Google Scholar with the keywords SDGS, Santri and those related to research. This research found several things that students (santri) play a significant role in supporting sustainable development goals (SDGs) by receiving both religious education and skills training in various fields, preparing them to face societal life and create independent businesses. Some strategies for developing life skills in pesantren include a life skills-based curriculum, strengthening the student entrepreneurship program, educational innovation to enhance student competitiveness, and collaboration with stakeholders in supporting the SDGs. Islamic boarding schools (pesantren) are expected to develop life skill-based strategies to enhance the quality of education, alleviate poverty, and provide decent employment opportunities for the students.